The Effect of Profitability, Growth, and Corporate Governance Mechanisms on Financial Distress in Mining Companies Listed in BEI - Yuza Dwi Putri Yuza Dwi Putri; Erni Masdupi (Universitas Negeri Padang, 2022)
This studys aims to analyze the effect off profitability, growth, and corporate governance mechanisms on financial distress in mining companies listed on the Indonesia Stock Exchange. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2014-2019. The sampling technique used purposive sampling technique with a total sample of 90 samples. The type of data used in this study is secondary data obtained by the Indonesia Stock Exchange (IDX) and the sample company annual reports. The analytical method used is multiple linearregression. The results of the study conclude that profitability, growth and the board of commissioners have an effect on financial distress. Meanwhile, managerial ownership, institutional ownership, and audit committee have no effect on financial distress.